Path Loss Characterization in an Indoor Laboratory Environment at 3.7 GHz in Line-Of-Sight Condition - Avella-Cely, Sandy Enrique; Muñoz-Pérez, Juan Carlos; Fernández-González, Herman Antonio; Rubio-Arjona, Lorenzo; Reig-Pascual, Juan Ribera; Rodrigo-Peñarrocha, Vicent Miguel (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of this work is to propose experimental path loss propagation models for communication channels in indoor environments. In this sense, an experimental path loss characterization has been achieved, according to the measurements campaign carried out in a typical scenario of a university campus. These narrowband measurements were collected in the laboratory environment at 3.7 GHz in line-of-sight (LOS) condition. Also, these measurements were carried out at night to simulate stationary channel conditions. Thus, the results obtained show the values of the parameters of the close-in (CI) free space reference distance and floating-intercept (FI) path loss models, in terms of the transmitter and receiver separation distance. It should be noted that these values of the path loss models have been extracted applying linear regression techniques to the measured data. Also, these values agree with the path loss exponent values presented by other researchers in similar scenarios. The path loss behavior can be described with the implementation of these models. However, more measurement campaigns are needed to improve the understanding of propagation channel features, as well as to obtain better precision in the results obtained. This, in order to optimize the deployment and performance of next fifth-generation (5G) networks that combine indoor environments to offer their services and applications.